Case report: Complete cast formation of the entire intrahepatic biliary tree - Wang, Pusen; Zhong, Lin; Zhao, Dong (Frontiers in Medicine, 2025)
Biliary complications pose substantial challenges in liver transplantation (LT), particularly with regard to non-anastomotic strictures (NASs). Among these ischemic-type biliary complications, bile cast syndrome (BCS) is a particularly severe condition. Currently, there are limited data on the formation of complete hepatic casts in BCS. In this case report, we present a unique instance of a second LT involving the formation of a complete hepatic bile cast and discuss its diagnostic and therapeutic process. This case aims to enhance the understanding of the anatomical and pathological features of BCS.